If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 2x + x + 4 Reorder the terms: -2 + 4x = 2x + x + 4 Reorder the terms: -2 + 4x = 4 + 2x + x Combine like terms: 2x + x = 3x -2 + 4x = 4 + 3x Solving -2 + 4x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 4x + -3x = 4 + 3x + -3x Combine like terms: 4x + -3x = 1x -2 + 1x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 1x = 4 + 0 -2 + 1x = 4 Add '2' to each side of the equation. -2 + 2 + 1x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 4 + 2 1x = 4 + 2 Combine like terms: 4 + 2 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 | | 8-w=8 | | h=81.688+2.392*50.1 | | 3(6+5y)= | | a^2-169=0 | | 10x+1=-9 | | 8senx-3=0 | | F(t)=-16t^2+45t+6 | | -8x-8+2x=-2x | | (180-x)+(90-x)=210 | | 3x^2-8x-340=0 | | (n-8)-(2n+2)= | | 15x-4=x-1 | | 3(-2m+5)=-4m+9-m | | 10+0.07(15x)+9=15x | | 3x+8(2x-6)=2+12x | | 10x^2+1000=0 | | 3y-4=4 | | (22x)(x)+8x+840=0 | | 11(7)-3=7(7)+25 | | 4x^2-5=43 |